Oncolytic Viruses Partner With T-Cell Therapy for Solid Tumor Treatment - Rosewell Shaw, Amanda; Suzuki, Masataka (Frontiers in Immunology, 2018)
Adoptive T-cell immunotherapies, including chimeric antigen receptor-modified T-cells (CAR-T cells), have revolutionized cancer treatment, especially for hematologic malignancies. Clinical success of CAR-T cell monotherapy in solid tumors however, has been only modest. Oncolytic viruses provide direct cancer cell lysis, stimulate systemic immune responses, and have the capacity to provide therapeutic transgenes. Oncolytic virotherapy has shown great promise in many preclinical solid tumor models and the first oncolytic virus has been approved by the FDA for the treatment of advanced melanoma. As monotherapies for solid tumors, oncolytic virotherapy provides only moderate anti-tumor effects. However, due to their complementary modes of action, oncolytic virus and T-cell therapies can be combined to overcome the inherent limitations of each agent. This review focuses on the aspects of oncolytic viruses that enable them to synergize with adoptive T-cell immunotherapies to enhance anti-tumor effects for solid tumors.